Colorectal cancers survivors' adherence to lifestyle recommendations and cross-sectional associations with health-related quality of life. Issue 2 (16th April 2018) - Breedveld-Peters, Jose J. L.; Koole, Janna L.; Müller-Schulte, Eloise; van der Linden, Bernadette W. A.; Windhausen, Cherelle; Bours, Martijn J. L.; van Roekel, Eline H.; Weijenberg, Matty P.
Abstract: The lifestyle recommendations of the World Cancer Research Fund (WCRF)/American Institute for Cancer Research (AICR) are primarily intended for cancer prevention. In the absence of specific recommendations for cancer survivors, we investigated adherence of colorectal cancer (CRC) survivors to the WCRF/AICR lifestyle recommendations and associations with health-related quality of life (HRQoL). The cross-sectional part of the Energy for life after ColoRectal cancer (EnCoRe) study was conducted in 155 CRC survivors (stage I-III), 2–10 years post diagnosis. Dietary intake, physical activity and general body fatness were measured by 7-d food diaries, by questionnaires and accelerometers and BMI, respectively. Adherence to each of the ten WCRF/AICR recommendations was scored as 0 (no/low adherence), 0·5 (moderate adherence) or 1 point (complete adherence), and summed into an overall adherence score (range: 0–10). HRQoL, disability and distress were assessed by validated questionnaires. Associations of the overall WCRF/AICR adherence score with HRQoL outcomes were analysed by confounder-adjusted linear regression. The mean adherence score was 5·1 (sd 1·4, range: 1·5–8·5). In confounder-adjusted models, a higher adherence score was significantly associated with the HRQoL dimension better physical functioning ( β per 1 point difference in score: 2·6; 95 % CI 0·2, 5·1) and with less fatigue ( β : −3·3; 95 % CI −6·4, −0·1). In conclusion, higher adherence of CRC survivors to WCRF/AICR lifestyle recommendations for cancer prevention was associated with better physical functioning and with less fatigue. This study adds to the limited knowledge on adherence to lifestyle behaviours in CRC survivors and relationships with quality of life. Prospective studies are needed to investigate longitudinal associations.